Analysis of Determining Factors of Patient Satisfaction Physiotherapy in Partner Medika General Hospital Tanjung Mulia Medan - Mahmud Ar Rasyid Ridho Siregar; Arifah Devi Fitriani; Samsidar Sitorus (Journal La Medihealtico, 2022)
The purpose of this research is to examine the variables of patient satisfaction with physiotherapy at Tanjung Mulia General Hospital in Medan in 2021. This study used a Cross-Sectional research design. In this research, the population consisted of 2,337 physiotherapy patients, and the number of patients randomly sampled was 93. The two techniques of data collecting are primary data and secondary data. The data are analyzed using multivariate analysis and a binary logistic regression test. The findings revealed an interaction impact of physiotherapist (sig-p = 0.001), facility (sig-p = 0.013), and registration procedure (sig-p = 0.024), with organization (sig-p = 0.000) having the greatest significant influence on patient satisfaction (OR = 45,715). The value of Coefficient B, which is 3.822, is positive, indicating that patient satisfaction will be higher the better the business is at delivering services. The outcome of the research is that organization is the most influential element in determining the happiness of physiotherapy patients, followed by the interaction between physiotherapists, amenities, and the registration procedure. Suggestions to enhance the organization of physiotherapy services and develop positive relationships, comprehensive facilities, and a streamlined registration procedure so that physiotherapy patients are content with the services they get.